Modulatory Effect of Electroacupuncture on Isoflurane Anaesthesia in Cats - Wahyuni, Sri; Soehartono, R Harry; Siswandi, Riki (Jurnal Medik Veteriner, 2025)
This study aimed to evaluate the combination of electroacupuncture (EA) and isoflurane as an anesthetic regimen in domestic cats. A total of 15 cats were divided into two groups, namely tiletamine-zolazepam (TZ) (n = 5) and EA (n = 10). Atropine was used as a premedication, injected 5 min before the induction of TZ. Approximately 10 min after induction, endotracheal intubation was applied, and cats were connected to isoflurane anesthesia. EA was applied to the EA group during the first 10 min of the total 30 min under isoflurane maintenance. Furthermore, the acupuncture points ST-36 and SP-6 were used at a frequency of 80 Hz and an intensity of 4 mA. The quality of anesthesia was evaluated by several parameters, including isoflurane requirements, anesthesia quality, cardiovascular function, and respiratory function. Data were collected every 10 min for a total of 30 min from the time of isoflurane application, followed by analysis using a t-test with Welch’s correction. The results showed that there was a significant reduction in isoflurane requirement in EA group, as indicated by the area under the curve (AUC) (p = 0.0003). Isoflurane concentration at 10 min was significantly lower in EA group (1.25 ± 0.71) than in TZ group (2.1 ± 0.22). It was also significantly lower at 20 min in EA group (1.05 ± 0.79) than in TZ group (1.8 ± 0.27). In conclusion, the addition of EA effectively reduced isoflurane requirements while maintaining a similar quality and safety of anesthesia in both groups.